2013
DOI: 10.3390/v5010162
|View full text |Cite
|
Sign up to set email alerts
|

Base Composition and Translational Selection are Insufficient to Explain Codon Usage Bias in Plant Viruses

Abstract: Viral codon usage bias may be the product of a number of synergistic or antagonistic factors, including genomic nucleotide composition, translational selection, genomic architecture, and mutational or repair biases. Most studies of viral codon bias evaluate only the relative importance of genomic base composition and translational selection, ignoring other possible factors. We analyzed the codon preferences of ssRNA (luteoviruses and potyviruses) and ssDNA (geminiviruses) plant viruses that infect translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 64 publications
(79 reference statements)
4
23
0
Order By: Relevance
“…Their study suggests that mutational bias is the major determinant of codon usage variation amongst the plant viruses [1]. Cardinale et al 2013 concluded that complex senondary structures, genomic variation and host shifting can be the possible reasons of codon usage bias at specific sites in ssRNA viruses. They also suggest that base composition and translational selection cannot reveal the CUB in begomoviruses [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study suggests that mutational bias is the major determinant of codon usage variation amongst the plant viruses [1]. Cardinale et al 2013 concluded that complex senondary structures, genomic variation and host shifting can be the possible reasons of codon usage bias at specific sites in ssRNA viruses. They also suggest that base composition and translational selection cannot reveal the CUB in begomoviruses [9].…”
Section: Discussionmentioning
confidence: 99%
“…Cardinale et al 2013 concluded that complex senondary structures, genomic variation and host shifting can be the possible reasons of codon usage bias at specific sites in ssRNA viruses. They also suggest that base composition and translational selection cannot reveal the CUB in begomoviruses [9]. Belalov and Lukashev 2013 address the questions that the origin of nucleotide bias remains unknown, also they suggest that boot scanning consisting alignment of multiple genomes and other corresponding criteria's are needed to analyze local CUB.…”
Section: Discussionmentioning
confidence: 99%
“…It must be considered that both genetic drift derived from the mutation pressure and natural selection detected for A. coronavirus could also harbor some relationship with genomic RNA secondary structure constraints and not only codon usage, as synonymous 3rd base mutations, though synonymous in terms of amino acid codification, could result in altered RNA secondary structure (Cardinale et al, 2013) and, consequently, impaired viral transcription, replication and assembly. As signals for RNA replication and genome packaging in coronaviruses are RNA secondary structuredependent (Narayanan and Makino, 2007;Williams et al, 1999), such structures must be under intense evolutionary constraints that balance with codon usage evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Certain case studies have evidenced that the selective pressure plays an important role on the CUB of viral genes, for example, duck and human hepatitis viruses , small non-enveloped viruses (Shi et al, 2013), foot-and-mouth disease virus (Zhou et al, 2010), HIV (Pandit & Sinha, 2011), etc. In addition, the mutation pressure, genomic architecture, and secondary structure of genes could also constrain the codon usages of virus (Cardinale et al, 2013;Hershberg & Petrov, 2008;Sharp et al, 1993). For example, the variation in the number of hydrogen bonds between codons GAA and GAG for Glu (synonymous transition substitution) distinctive in clade 1 and clade 2, respectively (Table 4), could affect the formation of short doublestranded helices.…”
Section: Divergences Driven By Positive Selectionmentioning
confidence: 99%